(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study is primarily concerned with the use of moving mesh methods for the approximate solution of non-linear partial differential equations of parabolic type. Such methods have become a popular means for the solution of problems which may contain sharp features that are hard to approximate. Whilst efficiently managing computational overheads. Initially, a novel moving grid technique known as Contour Zoning is discussed. This ’static’ method is able to reduce numerical resources by grouping together sets of nodes as a moving contour of the solution.